KLAUDIJUS MANIOKAS, ED., LITHUANIA’S FIRST DECADE IN THE EUROPEAN UNION: TRANSFORMATION OR IMITATION? - Lašas, Ainius (Baltic Journal of Political Science, 2017)
For those who want to better grasp the political and socio-economic trajectory of Lithuania since its accession to the EU, this edited volume provides a wealth of information and insights. It touches upon a variety of themes ranging from the politicization of LGBT rights to Lithuania’s bumpy road to the eurozone. While this constitutes an interesting and informative read, the book sometimes struggles to maintain theoretical and conceptual cohesion throughout all chapters. [...]